2017
DOI: 10.18176/jiaci.0155
|View full text |Cite
|
Sign up to set email alerts
|

Adult Atopic Dermatitis: Less Certainty, More Challenges

Abstract: We read with great interest the recent article by Silvestre Salvador et al [1] concerning the clinical and diagnostic challenges posed by adult atopic dermatitis (AD). We completely agree with the authors that the numerous problems faced by dermatologists and allergologists during the complex diagnostic and treatment process remain unresolved. Indeed, we previously underlined the need for specific and validated diagnostic criteria for adult AD in order to improve diagnostic accuracy and to gain more detailed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
1
1
0
1
Order By: Relevance
“…We found the preliminary results reported by Megna et al [1] to be very interesting. The authors found that onset of atopic dermatitis was during adulthood in 40.3% of patients.…”
Section: To the Editorsupporting
confidence: 63%
“…We found the preliminary results reported by Megna et al [1] to be very interesting. The authors found that onset of atopic dermatitis was during adulthood in 40.3% of patients.…”
Section: To the Editorsupporting
confidence: 63%
“…Considering this scenario, better definition of diagnostic criteria for adult onset ad is needed in order to avoid both misdiagnosis and/or undertreatment in adult patients. [25][26][27][28] In fact, despite significant advances in our understanding of the etiology and pathogenic mechanisms underlying AD, at present no markers are available that can help clinicians in routinely reaching a definitive diagnosis of ad. 1 to address these issues and provide practical guidance for clinicians to reliably diagnose ad in adult patients, representatives from three Italian dermatology scientific societies [Italian Society of Dermatology and Venereology (SidemaSt), italian association of Hospital dermatologists (adoi), italian Society of allergological, occupational and Environmental Dermatology (SIDAPA)] carried out a joint consensus meeting.…”
mentioning
confidence: 99%
“…Больные атопическим дерматитом (АД) составляют более 3% (а по некоторым данным -до 40%) взрослого населения развитых стран [1,2], при этом наблюдается постоянный рост заболеваемости и утяжеление форм течения АД. Среди аллергических заболеваний на долю АД приходится 50-60% [3].…”
Section: Introductionunclassified